A Factors Influencing the Incidence of Premature Rupture of Membrane (Prom) in Maternity Mothers - hipni, rubiati; Isnawati, Isnawati (Midwifery Departement Poltekkes Kemenkes Banjarmasin, 2023)
Abstract Premature rupture of membranes (KPD) or Premature Rupture Of The Membrane (PROM) is a rupture of the membranes before delivery if the opening in primi is less than 3 cm and in multi it is less than 5 cm. Based on the latest data obtained at Idaman Banjarbaru Hospital, mothers who experienced KPD in 2016 were 145 mothers with KPD out of 1594 mothers giving birth (9%) and in 2017 there was an increase of 242 mothers experiencing KPD out of 1974 mothers giving birth (12.25%). This study aimed to discover the factors that influence the incidence of premature rupture of membranes (PROM) in women giving birth. Research method: The research design used in this research is descriptive. The population in this study were all mothers with premature rupture of membranes at Idaman Banjarbaru Hospital in 2017 as many as 242 people. The sampling technique used systemic random sampling with a total sample of 152 people—a collection tool for medical record data documentation. The analysis used is univariate analysis with a percentage formula. The results showed that the number of mothers giving birth with KPD based on the causal factors at Idaman Banjarbaru Hospital in 2017 was caused by abnormalities in the location of the fetus as many as 8 people (5.3%), age factor <20 &> 35 years as many as 34 people (22.4%) ), parity factors 1&>4 were 80 people (52.6%), and multiple pregnancy factors were 6 people (3.9%). Suggestions for routine ANC in pregnant women and the need for further research on other factors that can cause premature rupture of membranes. Keywords: Factors, KPD, mothers giving birth